2003
DOI: 10.1007/s00404-002-0467-4
|View full text |Cite
|
Sign up to set email alerts
|

Water birth: microbiological colonisation of the newborn, neonatal and maternal infection rate in comparison to conventional bed deliveries

Abstract: Neonatal outcome, infantś and maternal infection rate did not differ between the three groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 8 publications
1
32
0
Order By: Relevance
“…Results of 10 studies measuring 5‐minute Apgar scores reported no differences after underwater or conventional births, whereas 4 studies reported significantly higher scores among neonates born in water . Four studies measured 10‐minute Apgar scores, and all reported no differences regardless of birth place . In summary, available evidence suggests there is no difference in one‐ and 10‐minute Apgar scores after waterbirth versus conventional birth; and 5‐minute scores may be similar or higher after waterbirth in healthy study populations.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Results of 10 studies measuring 5‐minute Apgar scores reported no differences after underwater or conventional births, whereas 4 studies reported significantly higher scores among neonates born in water . Four studies measured 10‐minute Apgar scores, and all reported no differences regardless of birth place . In summary, available evidence suggests there is no difference in one‐ and 10‐minute Apgar scores after waterbirth versus conventional birth; and 5‐minute scores may be similar or higher after waterbirth in healthy study populations.…”
Section: Resultsmentioning
confidence: 90%
“…Two studies did not specify the time at which scores were measured, which is critical for interpretation given that one‐minute scores have no long‐term clinical significance in the absence of other findings . Overall, results suggest there is no difference in Apgar scores after waterbirth versus conventional birth . However, some disparate findings were observed for scores at one minute: 8 studies reported no difference, 2 studies found significantly higher scores after waterbirth, and one study found lower scores after waterbirth .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, Geissbuehler et al 10 and Thoeni et al 11 found that waterbirth decreases the number of episiotomies and perineal lacerations. In relation to neonatal outcomes, one study showed a significant increase in neonatal arterial blood pH and an increased Apgar score 10 ; however, three other studies showed no differences in either 9,11,13 …”
Section: Introductionmentioning
confidence: 98%
“…[72] In a microbiological study, comparing neonatal bacterial colonization after water birth to conventional bed deliveries with or without relaxation bath showed no significant difference between three groups in neonatal outcome, infant's and maternal infection rate. [73]…”
Section: Introductionmentioning
confidence: 99%